Validated High Performance Liquid Chromatographic Method for Estimation of Nisoldipine from Matrix Type Transdermal Films: Application to Ex vivo Skin Permeability Studies (Asian Journal of Pharmaceutics (AJP), 2017)
Context: Assessment of nisoldipine (NSP) skin flux using validated high-performance liquid chromatographic (HPLC) method. Aim: A validated HPLC method was developed for estimation of NSP in skin permeated samples from matrix type transdermal films. Materials and Methods: Chromatographic separation was done using Phenomenex Luna C18 column (150 mm Ã— 4.6 mm i.d. 5 Î¼m) employing acetonitrile:water:methanol (40:35:25 v/v) as the mobile phase. Settings and Design: The calibration solutions were prepared in the linearity range of 0.250-50 Î¼g/mL. The flow rate was maintained at 0.8 mL/min at 25Â°C. 10 Î¼L samples were injected and were monitored using photodiode array detector at a wavelength of 275 nm. Results: The limit of detection and limit of quantification for NSP were recorded as 0.125 Î¼g/mL and 0.150 Î¼g/mL, respectively. The correlation coefficient (r2) values for intraday and interday were >0.998 and % relative standard deviation values were